Análisis de la situación de los tratamientos para dejar de fumar basados en terapia cognitivo-conductual y en parches de nicotina - García Vera, María Paz; Sanz, Jesús (Psicooncología, 2006)
Over the last 10-15 years or so, there has been a stagnation of research in cognitive behavioural therapy (CBT) for smoking cessation and an increase of research in pharmacological therapy, while part of scientific community seems biased towards pharmacological therapy and against CBT. The aim of the present study was to test whether that situation reflects the efficacy of clinical treatments for smokers. After reviewing and re-analyzing two previous meta-analyses and new empirical studies, results pointed out that, according to abstinence rates at post-treatment and 6- and 12-month follow-ups, CBT, administered alone or in combination with nicotine patches, is more efficacious than nicotine patches administered alone. Therefore, nicotine patches should always be used in combination with CBT to maximize their efficacy.